Phytolith assemblages in the leaves of Guadua bamboo in Amazonia - Kalliola R.; Linna A.; Toiviainen L.; Ruokolainen K. (Kerala Forest Research Institute, 2022)
Abstract: We studied phytoliths (plant stones) from 228 leaf samples of Guadua weberbaueri and Guadua sarcocarpa bamboos from eleven collection locations in Southern Peruvian Amazonia and in the state of Acre in Brazil. Four leaf-blade transverse thin sections were made by grinding and smoothing them into a 30 µm thickness, and over 550 phytolith slides created by using both the dry ashing and wet oxidation methods. Large-sized (up to 50 µm) cuneiform bulliform cells in the intercostal adaxial leaf-blade areas were the most conspicuous phytoliths in Guadua leaves, but their abundance varied even locally. Other recurrent phytolith types included bilobate, saddle, and rondel shaped short cells; long cells in many different sizes and ornamentations; and prickle hairs, spikes, stomatal, and inter-stomatal cells. We found the definite classification of phytoliths into morphotypes difficult because of their variable sizes, forms, and surface characteristics. Conjoined tricellular cell structures with one to three mineral-accumulating cells forming a characteristic mushroom-like constellation were also documented. Fusoid cells forming dense rows attached to the costal zones locally showed mineralization, indicating their role in inorganic mineral mobilization and deposition in Guadua leaves. Foliar phytolith assemblages showed little variation among the different collection locations compared to the variation found among leaves within individual sites.
Keywords: Amazonia, bamboo, fusoid cell, Guadua, leaf, phytolith